The status quo of short videos as a health information source of Helicobacter pylori: a cross-sectional study - Lai, Yongkang; Liao, Foqiang; He, Zixuan; Lai, Weiguo; Zhu, Chunping; Du, Yiqi; Li, Zhaoshen (Frontiers in Public Health, 2024)
Background: Health education about Helicobacter pylori (H. pylori) is one of the most effective methods to prevent H. pylori infection and standardize H. pylori eradication treatment. Short videos enable people to absorb and remember information more easily and are an important source of health education. This study aimed to assess the information quality of H. pylori-related videos on Chinese short video-sharing platforms. Methods: A total of 242 H. pylori-related videos from three Chinese short videosharing platforms with the most users, TikTok, Bilibili, and Kwai, were retrieved. The Global Quality Score (GQS) and the modified DISCERN tool were used to assess the quality and content of videos, respectively. Additionally, comparative analyses of videos based on different sources and common H. pylori issues were also conducted.The median GQS score and DISCERN score was 2 for H. pylori-related videos analyzed in this study. Non-gastroenterologists posted the most H. pylori-related videos (136/242, 56.2%). Videos from gastroenterologists (51/242, 21.0%) had the highest GQS and DISCERN scores, with a median of 3. Few videos had content on familybased H. pylori infection control and management (5.8%), whether all H. pyloripositive patients need to undergo eradication treatment (27.7%), and the adverse effects of H. pylori eradication therapy (16.1%). Conclusion: Generally, the content and quality of the information in H. pylori-related videos were unsatisfactory, and the quality of the video correlated with the source of the video. Videos from gastroenterologists provided more correct guidance with higherquality information on the prevention and treatment of H. pylori infection.